FORMULASI BISKUIT LAKTOGENIK BERBASIS PANGAN LOKAL TEPUNG TALAS (Colocasia Esulenta L. Schott) DENGAN SUBSTITUSI TEPUNG DAUN KATUK (Sauropus Androgynus L. Merr) SEBAGAI ALTERNATIF PMT IBU MENYUSUI - Mulyanita; Ayu Rafiony; Ismi Trihardiani; Dedi Satria; Jurianto Gambir (Postgraduate, University of Mataram, 2025)
The study explores the potential of utilizing talas tuber flour (Colocasia Esculenta L. Schott) and katuk leaf flour (Sauropus androgynus L. Merr) in biscuit production to enhance nutritional value and promote lactation in breastfeeding mothers. Talas, rich in complex carbohydrates, fiber, minerals, and vitamins, and katuk leaves, high in protein, vitamins A and C, iron, and lactogenic active substances, were used to develop biscuits in three different formulations: F1 (95%: 5%), F2 (90%: 10%), and F3 (85%: 15%). The organoleptic test identified F1 as the best formulation, and proximate analysis showed that F1 contained 6.14% moisture, 2.52% ash, 27.04% fat, 8.59% protein, 50.3% carbohydrates, and 6.70% crude fiber. The biscuits also contained 0.209% phosphorus, 80.4 mg/kg iron (Fe), and 142 mg/kg calcium (Ca). These findings suggest that biscuits made from talas tuber and katuk leaf flour can be a valuable nutritional supplement, potentially aiding in the improvement of breast milk production.